OPTIMASI ALAT GALI MUAT DAN ALAT ANGKUT TERHADAP PRODUKSI BATUBARA DENGAN METODE KAPASITAS PRODUKSI DAN METODE TEORI ANTRIAN PADA PIT TAMAN PERIODE OKTOBER 2016 UNIT PERTAMBANGAN TANJUNG ENIM PT. BUKIT ASAM (PERSERO) Tbk. - Alifa Alifa; Mulya Gusman; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2018)
Equipment is a very important factor in ensuring the sustainability of mining production. Theamount of excess fleet will result in inflated operating expenses, while the number of fleetsthat little will reduce the number of mine production. Ideal conditions in the process ofloading and transportation of materials is very difficult to achieve. However, it can beattempted through efficiency tehadap number of major mining dump truck. One simulationmethod that can be used to optimize the production of electric load - dump truck main methodis to use the production capacity and queuing theory. Simulations conducted in order toobtain optimum number of trucks with truck queuing time the minimum and avoid waiting forthe appliance load dump truck.Unloading tool used was Excavator Backhoe Komatsu PC 400 consist of 2 units. Dump truckwhich is a truck used Hino 500 FM 320 TI totaling 12 units. Based on simulation results withsimulation approach production capacity dump truck takes 11 units while the dump truckqueues based on the theory that it takes 11 units. In actual dump truck used is 12 units.Keywords : excavator, dump truck, match factor, production optimize, queuing theory